2020
DOI: 10.1088/1755-1315/418/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fruit and bunch of mapanget tall and Indonesia coconut hybrid with several planting distance using AMMI model and GGE biplot analysis

Abstract: Coconut plantations with new system of planting distance allow wider use of distance under the coconut than the conventional planting distance. Evaluation stability ofMapanget coconut (DMT) and KHINA hybrid coconut at various planting distance systems can be used as a recommendation for the development of coconuts with new planting distance in the most suitable environmental conditions. The purpose of this study was to determine the stability of the yields of DMT and KHINA grown with various distance models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Only one test environment (Bako) is both representative and discriminating, making it a good place to nd genotypes that are generally adapted. Similar results as many authors Y Matana [4]; SALEEM [26], Dagnechew [27], Ndlala [28], Dao [29] and Moges [30], who used GGE biplot to identify high representativeness and discriminating for different crops.…”
Section: Gge Biplot Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…Only one test environment (Bako) is both representative and discriminating, making it a good place to nd genotypes that are generally adapted. Similar results as many authors Y Matana [4]; SALEEM [26], Dagnechew [27], Ndlala [28], Dao [29] and Moges [30], who used GGE biplot to identify high representativeness and discriminating for different crops.…”
Section: Gge Biplot Analysissupporting
confidence: 87%
“…The multiplicative effects analysis (Table 4) revealed that the AMMI model with test environment contributed 55.78 percent of the total variation of sum square for grain yield, while G and G x E sources of variation accounted for 7.88 percent and 14.55 percent, respectively. Other research has found that in multi-environment trials, location accounts for the vast majority of total variation, with genotype and G x E accounting for only a minor portion [4,5,15]. In Table 4, AMMI revealed that the rst two hybrids (G11, G12) were the best performers in each environment, while CK1 was the worst performer.…”
Section: Ammi Analysismentioning
confidence: 88%
See 2 more Smart Citations